KAPITALISME INTERNASIONAL DAN FENOMENA PENJARAHAN LAHAN DI INDONESIA - Poltak Partogi Nainggolan (Sekretariat Jenderal DPR RI, 2013)
Land grabbing phenomena tends to increasingly occur today in many regions of Indonesia while at the same time MNCs activities and investments dramatically increase, and productive land tends to rapidly decrease. Indonesia, a country which consists of large land area, is seriously threatened by fast land conversion in order to deal with the demand of international capitalism. This essay is resulted from an analytical and a descriptive research conducted in 2013 by applying a qualitative methode. Field researches are conducted in West Papua and East Nusa Tenggara provinces. Its research findings reveal that the fast land conversion caused by the emergence of new palm oil plantation, the development of new infrastructure, exploitation of natural resources, especially mining. Further findings shows several impacts of land grabbing, namely environmental degradation, food crisis, and the emergence of social conflicts. The involvement of state apparatus in land grabbing process and poor law enforcement are also disclosed and discussed in this essay.